Spatially Distribution of Quercus semecarifolia in Rasuwa District Using GIS and RS - Shrestha, Ila (International Journal of Applied Sciences and Biotechnology, 2015)
The paper is based on the case study of Rasuwa district, is a land of geographical extremes, ranging from 600 m Betrabati river to 7234 m Langtang Lirung, the highest point in the northwest. The study was carried out on the detection of Quercus semecarifolia J.E.Smith using Remote-Sensing and Geographic Information System technique. SPOT Image and ERDAS Software have used for the image processing. The program has detected the different types of ecological parameters in tropical to alpine zone and specified the plant species in the study after ground truthing. Int J Appl Sci Biotechnol, Vol 3(4): 747-749